2021
DOI: 10.1136/bjsports-2019-101970
|View full text |Cite
|
Sign up to set email alerts
|

Management of plantar heel pain: a best practice guide informed by a systematic review, expert clinical reasoning and patient values

Abstract: ObjectiveTo develop a best practice guide for managing people with plantar heel pain (PHP).MethodsMixed-methods design including systematic review, expert interviews and patient survey.Data sourcesMedline, Embase, CINAHL, SPORTDiscus, Cochrane Central Register of Controlled Trials, trial registries, reference lists and citation tracking. Semi-structured interviews with world experts and a patient survey.Eligibility criteriaRandomised controlled trials (RCTs) evaluating any intervention for people with PHP in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 67 publications
1
82
0
3
Order By: Relevance
“…7 Other conservative interventions for foot conditions are available, such as magnetized insoles (cushioned insoles with magnetic foil embedded in the foam under the proximal arch), 8 prefabricated heel lifts, 9 and resting night splints (braces that hold the foot in place, with the toes pointed up). 1 Custom-made orthotics improve plantar pressure redistribution and gait mechanics 8,10,11 However, a 2020 CADTH report 12 found inconsistencies regarding the effectiveness of customized or prefabricated foot orthotics compared to control interventions (standard insole, placebo, or none) in alleviating pain and improving foot function in patients with chronic foot pain. Another CADTH 13 report from 2019 found no difference between custommade and prefabricated foot orthotics for pain reduction or functional improvement, based on a limited amount of evidence.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Other conservative interventions for foot conditions are available, such as magnetized insoles (cushioned insoles with magnetic foil embedded in the foam under the proximal arch), 8 prefabricated heel lifts, 9 and resting night splints (braces that hold the foot in place, with the toes pointed up). 1 Custom-made orthotics improve plantar pressure redistribution and gait mechanics 8,10,11 However, a 2020 CADTH report 12 found inconsistencies regarding the effectiveness of customized or prefabricated foot orthotics compared to control interventions (standard insole, placebo, or none) in alleviating pain and improving foot function in patients with chronic foot pain. Another CADTH 13 report from 2019 found no difference between custommade and prefabricated foot orthotics for pain reduction or functional improvement, based on a limited amount of evidence.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…Six systematic reviews, 1,5,7,8,27,28 5 RCTs, 9,[29][30][31][32] 1 economic evaluation, 33 and 2 evidence-based guidelines 34,35 were included in this report.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a previous study showed that steroid injection is the second most used therapy for managing shoulder pain by Australian general practitioners [16]. Despite the frequent use of these therapies, clinical practice guidelines for musculoskeletal conditions have not usually mentioned neither dry needling nor corticosteroid injections as first line treatment [17][18][19][20][21]. Some guidelines have recommended dry needling and corticosteroid injection as adjunct treatment for some musculoskeletal conditions such as plantar fasciitis and Achilles pain, but it is suggested to be used with caution [18,19,21].…”
Section: Introductionmentioning
confidence: 99%